The Importance of Wireless Capsule Endoscopy for Research into the Intestin al Absorption Window of 5-Aminosalicylic Acid in Experimental Pigs - Kvetina, Jaroslav; Tacheci, Ilja; Nobilis, Milan; Kopacova, Marcela; Kunes, Martin; Bures, Jan (Current Pharmaceutical Design, 2017)
Background: Absorption windows in particular segments of the small intestine can contribute to the development of orally administered drug formulations and can limit the bioavailability of released compounds. Objective: The aim of this study was to evaluate use of wireless capsule enteroscopy regarding the disintegration kinetic process of tablets in the small intestine and its comparison with the levels of the model drug (5- aminosalicylic acid; 5-ASA), and its majority metabolite (N-acetyl-5-aminosalicylic acid; N-acetyl-5-ASA) in blood plasma. Methods: Tablets were endoscopically introduced into the duodenum and their disintegration was monitored using wireless capsule enteroscopy in anaesthetised pigs. In parallel, blood plasma time profiles of the model drug (5-ASA) released from tablets and its metabolite (N-acetyl-5-ASA) were detected. Results: The disintegration of tablets was evident in the proximal jejunum (until the 90-minute mark) and culminated at the 3rd hour. The maximum plasmatic concentration of 5-ASA was reached at the 3rd hour and in the case of its metabolite (N-acetyl-5-ASA) at the 4th hour. Conclusion: The study demonstrated the advantage of combination of wireless capsule enteroscopy and bioanalytical determination of pharmacokinetic parameters in an animal experiment to localise the disintegration site of solid dosage form and following kinetics of intestinal absorption of the released active agent.
Keywords: wireless capsule enteroscopy